Fog-based caching in software-defined information-centric networks. (July 2018) - Al-Turjman, Fadi
Abstract: In this paper, we propose a cache replacement approach for Fog applications in Software Defined Networks (SDNs). Our approach depends on three functional factors in SDNs. These three factors are: age of data based on periodic request, popularity of on-demand requests, and the duration for which the sensor node is required to operate in active mode to capture the sensed readings. These factors are considered together to assign a value to the cached data in a software-defined network in order to retain the most valuable information in the cache for longer time. The higher the value, the longer the duration for which the data will be retained in the cache. This replacement strategy provides significant availability for the most valuable and difficult to sense data in the SDNs. Extensive simulations are performed to compare our approach against other dominant cache replacement policies under varying circumstances such as data popularity, cache size, network load, and connectivity degree.